2011
DOI: 10.1097/gco.0b013e328342f1f6
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus infections during pregnancy

Abstract: These findings suggest that serologic testing for CMV during pregnancy may be appropriate either using one-time testing or serial serologic testing throughout the first two trimesters of pregnancy and that education of pregnant women about CMV is necessary so that they can asses their risk and make informed choices about serologic screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 43 publications
0
46
0
14
Order By: Relevance
“…CMV transmission in the first trimester is associated with the poorest fetal outcome [3]. Enders et al indicated that the rate of symptomatically infected fetuses or newborns at birth was 22.8 % for any symptoms and 10.3 % for severe manifestation, but no symptoms were observed in infected newborns of mothers with primary infection in the preconceptional period and the third trimester [7].…”
Section: Pathogenesis Of Congenital CMV Infectionmentioning
confidence: 99%
See 4 more Smart Citations
“…CMV transmission in the first trimester is associated with the poorest fetal outcome [3]. Enders et al indicated that the rate of symptomatically infected fetuses or newborns at birth was 22.8 % for any symptoms and 10.3 % for severe manifestation, but no symptoms were observed in infected newborns of mothers with primary infection in the preconceptional period and the third trimester [7].…”
Section: Pathogenesis Of Congenital CMV Infectionmentioning
confidence: 99%
“…It is comprehensible that maternal preconceptional immunity against CMV gives relatively good protection to fetus, so a smaller proportion becomes infected. Preexisting humoral immunity protects seropositive pregnant women against CMV reinfection at a rate of 66-93 % [3]. The fetal outcome after congenital CMV infection is summarized in Figure 1.…”
Section: Pathogenesis Of Congenital CMV Infectionmentioning
confidence: 99%
See 3 more Smart Citations